PATTERNS OF EXTRAPULMONARY TUBERCULOSIS IN CHILDREN: A HOSPITAL BASED STUDY - Hatwal, Deepa; Chaudhari, Sheela; Joshi, Anil Kumar; Rathaur, Vyas Kumar (Indian Journal of Community Health, 2013)
Background: Extrapulmonary Tuberculosis is an important clinical problem, defined as the isolated occurrence of tuberculosis in any part of the body other than lungs. Aim of the study is to describe the various presentations of extrapulmonary tuberculosis cases in children of Uttarakhand. Method: The children below 15 years included in the study from the pathology and pediatrics department of VCSG Govt. Medical. Science and Research Institute Srinagar Garhwal, private pathological centers, nursing homes and clinics at Srinagar Garhwal,Uttarakhand , during October 2010 to March 2012. The cases are selected on the basis of cytopathological and histopathological findings suggestive of tuberculosis. Cytologically suggestive cases of tuberculosis were further reviewed for detailed clinical status, conventional tests and response to antitubercular treatment to categorize the different types of extrapulmonary tuberculosis. Result: Out of 250 suspicious cases, 58 (23.2%) cases were of extrapulmonary tuberculosis. Out of 58 cases, lymph node tuberculosis in 24 (41.3%) was commonest, followed by tubercular meningitis in 22.4%, pleural effusion in13.7%, musculoskeletal in12%,abdominal tuberculosis in 5.2 %, disseminated tuberculosis in 3.4% and cutaneous tuberculosis in only one case (1.7%). Cervical lymphnodes are the most common lymphnode involved (70.8%).Tissue cytology shows high sensitivity for acid fast bacilli on Ziehl- Neelsen staining. Fluid cytology showed high sensitivity (100%) for Adenosine deaminase (ADA) activity. All our cases responded to treatment and recovered well except two cases of tubercular meningitis. Conclusion: Although microbiological, and cyto-histopathological diagnosis are the gold standard but in our setup the patients having negative diagnostic test with strong clinical, radiographic and hematological investigations indicating tuberculosis were also treated on the line of tuberculosis. The diagnosis in latter was further strengthened by the positive response to the anti-tubercular treatment. Prompt and efficient identification of the source of transmission and application of effective environmental measures are intimately linked to the control of childhood tuberculosis.